PENGGUNAAN COOPERATIVE LEARNING PADA MATA PELAJARAN AKIDAH AHLAK UNTUK MENINGKATKAN KARAKTER ISLAMI SISWA : Penelitian di Madrasah Aliyah Se-KKM MAN 3 Cianjur - Tati Suminar (STAI Pelabuhan Ratu, 2020)
Furthermore, the implementation of the jigsaw method in learning Islamic Religious Education is very suitable, in addition to increasing student activity in the classroom, it can also improve student learning achievement. So students are able to understand and appreciate Islam well.Moreover, This study uses qualitative research in which data collected comes from interview scripts, field notes, personal documents, and other documents. The collected data were analyzed using descriptive analysis techniques. Looking closely at the data, the result of this research could be seen that the objectives, programs, implementation, results of the Jigsaw Learning method in learning Islamic Religious Education in Madrasah aliyah KKM 3 Cianjur, including MAN 3, MA Baiturohman, MA leles, and MA Al-Falah Campaka Cianjur, have been very admirable which is proven by the results expected by educators in the daily Islamic moral behavior of students. This method is very helpful for Islamic Religious Education (PAI) teachers because not only could it involve students actively, but also enhance student collaboration. Besides that, the application of this method is supported by several fairly complete facilities provided by the school.